The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1590/1806-9061-2022-1645
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citrus Flavonoid on Storage Time and Meat Quality of Pharaoh Quail (Coturnix Pharaoh)

Abstract: This study investigates the effects of Hesperidin added to quail ration at different rates on some microbiological and physicochemical, lipid peroxidation, and lipid profiles in thigh meat. The current study had a duration of 35 days and used Pharaoh quails (Coturnix Pharaoh). The grouping was done in three treatment groups: Control, HES500, and HES1000 (each group was divided into five subgroups), and 0, 500, and 1000 mg/kg of Hesperidin was added to the basal diet of the groups, respectively. Adding Hesperid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…Moreover, pH levels were higher in the Lav250 and Lav500 groups compared to the control group on the ninth day. In current study, quail meat pH values were within the range reported by similar studies (Genchev et al, 2010;Özbilgin et al, 2021, 2022. The oxidation products of unsaturated fats are acidic molecules such as hydroxyl acid, keto acid, and smaller fatty acid molecules (Belitz et al, 2004).…”
Section: Effect On Ph Parameter In Meatsupporting
confidence: 87%
“…Moreover, pH levels were higher in the Lav250 and Lav500 groups compared to the control group on the ninth day. In current study, quail meat pH values were within the range reported by similar studies (Genchev et al, 2010;Özbilgin et al, 2021, 2022. The oxidation products of unsaturated fats are acidic molecules such as hydroxyl acid, keto acid, and smaller fatty acid molecules (Belitz et al, 2004).…”
Section: Effect On Ph Parameter In Meatsupporting
confidence: 87%
“…Especially pH and aw are the main factors in meat quality. A high pH in meat is considered a sign of deterioration caused by bacterial activities [38,39]. Our study findings showed that bromelain supplementation did not have a statistically significant effect on the pH of meat.…”
Section: Discussionmentioning
confidence: 45%